“ISIM” DAN “ISI” DALAM PERSEMBAHAN SENI PERMAINAN KUDA KEPANG: (“ISIM” AND “ISI” IN THE ARTISTIC PERFORMANCE OF PERMAINAN KUDA KEPANG) - Siti Islamiah Ahmad; Mohd Effindi Samsuddin; Awang Azman Awang Pawi (Jurnal Pengajian Melayu (JOMAS), 2023)
Abstract The art of “permainan” Kuda Kepang is a type of dance that goes through a ritual process before reaching a trance state during the performance. The current study focuses on the keywords “isim” and “isi, which refers to the form of practice taken and performed by Kuda Kepang players. This investigation focuses on the relationship between the possession of “isim” within the player and the filling of “isi” in the Kuda Kepang equipment to realize the presence of the trance state during the performance. Therefore, the objective of this study is to identify the factors contributing to the occurrence of the trance state during the performance. The data in this research were obtained through field studies with four active Kuda Kepang groups in the state of Johor. The content and factors that cause the trance state are analysed based on the philosophy of the Kuda Kepang game containing the relevant element. The qualitative research design produced data obtained from observation, interviews, and documentation. The results of the investigation show that players who experience the trance state possess “isim”, while the performance equipment used has “isi”. The trance state has a close relationship with the ritual process performed before the performance, which is also related to the possession factor of “isim” and “isi”. Without “isim” within the player and “isi” in the music equipment, the trance state during the performance would not occur, even if the ritual has been performed. This study highlights the importance of “isim” and “isi” in the success of the ritual process and the occurrence of the trance state. Further research can be conducted on the possession of “isim” and the content of the “isi” in Kuda Kepang performances. Keywords: “isim”, “isi”, kuda kepang, ritual process, trance. Abstrak Seni permainan kuda kepang ialah sejenis tarian yang melalui proses ritual sebelum berlakunya keadaan trance (mabuk) dalam persembahan. Kajian ini merupakan pengkajian yang mengambil kata kunci “isim” dan “isi”, iaitu bentuk amalan yang diambil dan dilakukan oleh pemain permainan kuda kepang. Kajian ini berfokus kepada hubung kait antara pemilikan “isim” dalam diri pemain dan pengisian “isi” dalam peralatan permainan kuda kepang untuk merealisasikan kewujudan keadaan mabuk ketika persembahan. Oleh itu, objektif kajian ini ialah untuk mengenal pasti faktor berlakunya mabuk sewaktu persembahan. Data-data dalam kajian ini diperoleh melalui kajian lapangan bersama empat kumpulan kuda kepang yang masih bergerak aktif di negeri Johor. Kandungan dan faktor yang menyebabkan keadaan mabuk ini berlaku dikaji dalam kajian ini bertitik tolak daripada falsafah permainan kuda kepang yang mengandungi unsur tersebut. Reka bentuk kajian kes melalui kaedah kualitatif menghasilkan data yang diperolehi daripada pemerhatian, wawancara, dan dokumentasi. Hasil penelitian menunjukkan pemain yang mabuk memiliki “isim” dan peralatan persembahan yang digunakan pula memiliki “isi”. Keadaan mabuk mempunyai hubungan rapat dengan proses ritual yang dilakukan sebelum persembahan yang turut berkait rapat dengan dengan faktor pemilikan “isim” dan “isi” tersebut. Tanpa “isim” dalam diri pemain dan “isi” dalam peralatan muzik, keadaan mabuk sewaktu persembahan tidak akan berlaku walaupun proses ritual telah dijalankan. Melalui kajian ini, dapat dijelaskan kepentingan “isim” dan “isi” bagi menjayakan proses ritual dan kewujudan mabuk. Kajian lanjutan boleh dilakukan terhadap pemilikan “isim” dan kandungan “isi” dalam persembahan Permainan kuda kepang. Kata Kunci: “isim”, “isi”, kuda kepang, unsur mabuk, proses ritual